THE EFFECT OF PET ATTACHMENTS ON HAPPINESS IN PET OWNERS IN MEDAN CITY - Manalu, Fera Widiana Br. Boang; Aritonang, Nancy Naomi (STABN RADEN WIJAYA WONOGIRI, 2024)
This research aims to see the effect of pet attachments on the happiness of pet owners in the city of Medan . Based on research conducted by researchers with the research title The Influence of Pet Attachments on Happiness in Pet Owners in the City of Medan, it can be concluded that: The results of this study show that there is a significant influence of pet attachments on happiness in pet owners of 11.9%. If the value of variable X (Pet Attachment) increases, there will be an influence on variable Y (Happiness). This shows that there is a positive relationship, which means that the higher the pet attachment score, the higher the happiness and vice versa. The majority of pet owners in the city of Medan have pet attachments in the medium category and pet owners in the city of Medan experience more pet attachments in the form of animal rights/animal welfare. The majority of pet owners in the city of Medan have happiness in the high category and pet owners in the city of Medan experience more happiness in the form of full involvement.